Using interprofessional simulation to improve collaborative competences for nursing, physiotherapy, and respiratory therapy students. Issue 5 (2nd September 2016) - King, Judy; Beanlands, Sarah; Fiset, Valerie; Chartrand, Louise; Clarke, Shelley; Findlay, Tarra; Morley, Michelle; Summers, Ian
ABSTRACT: Within the care of people living with respiratory conditions, nursing, physiotherapy, and respiratory therapy healthcare professionals routinely work in interprofessional teams. To help students prepare for their future professional roles, there is a need for them to be involved in interprofessional education. The purpose of this project was to compare two different methods of patient simulation in improving interprofessional competencies for students in nursing, physiotherapy, and respiratory therapy programmes. The Canadian Interprofessional Health Collaborative competencies of communication, collaboration, conflict resolution patient/family-centred care, roles and responsibilities, and team functioning were measured. Using a quasi-experimental pre-post intervention approach two different interprofessional workshops were compared: the combination of standardised and simulated patients, and exclusively standardised patients. Students from nursing, physiotherapy, and respiratory therapy programmes worked together in these simulation-based activities to plan and implement care for a patient with a respiratory condition. Key results were that participants in both years improved in their self-reported interprofessional competencies as measured by the Interprofessional Collaborative Competencies Attainment Survey (ICCAS). Participants indicated that they found their interprofessional teams did well with communication and collaboration. But the participants felt they could have better involved the patients and their family members in the patient's care. Regardless of method of patient simulation used, mannequin or standardised patients, students found the experience beneficial and appreciated the opportunity to better understand the roles of other healthcare professionals in working together to help patients living with respiratory conditions.